UJI NEUROLOGICAL DEPRESSION DISORDERS INVENTORY FOR EPILEPSY (NDDI-E) PADA PASIEN EPILEPSI DI POLIKLINIK SARAF RSUP PROF. DR. R. D. KANDOU - Lengkoan, Joshua; Khosama, Herlyani; Sampoerno, Maja (Universitas Sam Ratulangi, 2015)
Abstract: Depression is a comorbid symptom that often occurs in epileptic patients. This study aimed to obtain the occurence of depression among epileptic patients at the Neurology Department Prof. Dr. R. D. Kandou Hospital Manado. This study used a cross-sectional design for diagnostic test. Respondents were all patients that came to the Neurology clinic at Neurology Department Prof. Dr. R. D. Kandou Hospital Manado. There were 30 epileptic cases during the period of October to November 2014 that fulfilled the inclusion and exclusion criteria. Based on the outcome of questionnaires distributed to respondents and the manual calculation with standardized score of Neurological Depression Disorders Inventory for Epilepsy (NDDI-E) >15, diagnosis of depression was confirmed. There were 10 depression cases among the 30 respondents. Conclusion: Neurological Depression Disorders Inventory for Epilepsy Indonesian Version could be used to detect depression disorders among epileptic patients.Keyword: epilepsy, depression, NDDI-EAbstrak: Depresi adalah salah satu gejala komorbid yang sering terjadi pada pasien epilepsi. Penelitian ini bertujuan untuk mengetahui gambaran depresi pada pasien epilepsi di Poliklinik Saraf RSUP Prof. Dr. R. D. Kandou Manado. Penelitian dilakukan menggunakan desain potong lintang untuk uji diagnostik dengan mengambil sampel semua pasien epilepsi yang datang ke Poliklinik Saraf BLU RSU Prof. Dr. R. D. Kandou Manado. Terdapat 30 pasien epilepsi yang berobat ke poliklinik saraf RSUP Prof. Dr. R. D. Kandou Manado bulan Oktober sampai November 2014 yang memenuhi kriteria inklusi dan ekslusi. Dari hasil kuesioner yang dibagikan kepada responden dan melalui hasil perhitungan manual dengan standar skor Neurological Depression Disorders Inventory for Epilepsy (NDDI-E) >15 diagnosis mengalami depresi ditetapkan. Hasil penelitian menunjukkan 10 dari 30 responden mengalami depresi. Simpulan: Neurological Depression Disorders Inventory for Epilepsy (NDDI-E) versi Bahasa Indonesia dapat digunakan dalam mendeteksi gangguan depresi pada pasien epilepsi.Kata kunci: epilepsi, depresi, NDDI-E